Conserved worldwide linkage disequilibrium in the human factor XI gene - Tarumi, T.; Martincic, D.; Whitlock, J.A.; Addy, J.H.; Williams, S.M.; Gailani, D. (Genomics, 2000)
We have identified, in four diverse human populations, five common single-nucleotide polymorphisms (SNPs) in the coding region of the gene for the blood coagulation protease factor XI. Each SNP has an allele frequency > 5% in at least one population. Three of the SNPs (C472T, A844G, and T1234C), spread out over approximately 10 kb of genomic DNA, are in marked linkage disequilibrium (LD) With one another (P < 10-4). Interestingly, haplotypes associated with the linked SNPs are conserved across all populations studied, despite significantly different allele frequencies between populations. The presence of such common, widely dispersed haplotypes could complicate the interpretation of LD studies and emphasizes the need for a better understanding of general patterns of LD to facilitate identification of genes for common disorders. (C) 2000 Academic Press.